Toluene inhalation in adolescent rats reduces flexible behaviour in adulthood and alters glutamatergic and GABAergic signalling. Issue 5 (9th November 2016) - Furlong, Teri M.; Duncan, Jhodie R.; Corbit, Laura H.; Rae, Caroline D.; Rowlands, Benjamin D.; Maher, Anthony D.; Nasrallah, Fatima A.; Milligan, Carol J.; Petrou, Steven; Lawrence, Andrew J.; Balleine, Bernard W.
Abstract: Toluene is a commonly abused inhalant that is easily accessible to adolescents. Despite the increasing incidence of use, our understanding of its long‐term impact remains limited. Here, we used a range of techniques to examine the acute and chronic effects of toluene exposure on glutameteric and GABAergic function, and on indices of psychological function in adult rats after adolescent exposure. Metabolomics conducted on cortical tissue established that acute exposure to toluene produces alterations in cellular metabolism indicative of a glutamatergic and GABAergic profile. Similarly, in vitro electrophysiology in Xenopus oocytes found that acute toluene exposure reduced NMDA receptor signalling. Finally, in an adolescent rodent model of chronic intermittent exposure to toluene (10 000 ppm), we found that, while toluene exposure did not affect initial learning, it induced a deficit in updating that learning when response‐outcome relationships were reversed or degraded in an instrumental conditioning paradigm. There were also group differences when more effort was required to obtain the reward; toluene‐exposed animals were less sensitive to progressive ratio schedules and to delayed discounting. These behavioural deficits were accompanied by changes in subunit expression of both NMDA and GABA receptors in adulthood, up to 10 weeks after the final exposure to toluene in the hippocampus, prefrontal cortex and ventromedial striatum; regions with recognized roles in behavioural flexibility and decision‐making. Collectively, our data suggest that exposure to toluene is sufficient to induce adaptive changes in glutamatergic and GABAergic systems and in adaptive behaviour that may underlie the deficits observed following adolescent inhalant abuse, including susceptibility to further drug‐use. Abstract : Toluene is a commonly abused inhalant but our understanding of its long‐term impact remains limited. Acute toluene exposure led to changes in glutamatergic and GABAergic metabolomics as well as the electrophysiological properties of NMDA receptors. Further, chronic adolescent toluene exposure results in long‐term maladaptive behavioural changes particularly in decision‐making accompanied by changes in subunit expression of both NMDA and GABA receptors. Such changes may underlie the deficits observed following adolescent inhalant abuse including susceptibility to further drug use.